Sulla illiceità dell'aborto - Gustavo Arosemena (Universidad Hemisferios, 2017)
Abortion is seen as an immoral and unjust act by many. Nonetheless these views are under pressure to conform to the learned opinion on abortion. A variety of prestigious in the field of applied ethics support abortion in one way or another. And it is a dogma of modern liberalism that even if one is personally opposed to abortion, one must accept the neutral solution of its public permissibility. The present article defends the thesis that abortion is immoral and unjust against these contentions. With regards to the moral status of abortion, it argues that the prohibition of abortion is off a piece with the prohibition of killing generally, which is characterized by protecting all human beings equally. With regards to the compatibility of abortion permissibility with liberalism, the article argues that such a compromise is not neutral, but heavily rigged in favor of the interests and world-views of abortion proponents.